MILITARY INTERVENTIONSAND THE NIGERIA FOURTH REPUBLIC: A REFLECTION DISCOURSE - Stella Ughulu Eghoikhunu; Ihaza Kayode (International Studies Journal)
Since independence, Nigeria's unity has been plagued and threatened by socio-economic, cultural, religious and political dichotomies, which has led to military intervention in the political sphere of the country, even after the return to civilian rule in May 1999, known as the Nigeria Fourth Republic. Military interventions in Nigeria’s civil matters have been vehemently kicked against by many scholars due to its negative effects on the society. The main objective of the paper is to assess military interventions in Nigeria fourth republic to identify the loopholes in the interventions.  The paper used secondary data from newspapers and the internet. The qualitative method of analysis was used for this study. It discovered that military interventions in the socio-political and civil matters in the Nigeria fourth republic is characterized by violations and infringements of civic rights, disobedience of court orders, total disregard of human dignity and destruction of live and properties. The study recommends that there should be a conscious effort on the part of leaders of the nation to improve the socio-economic development of the country and more funding and training of the agencies/forces responsible for internal security.